A Systematic Review on Achilles tendon Injuries Prevalence - Fatahi, Ali; Alizadeh, Razieh; Yousefian Molla, Razieh (Journal of Clinical Physiotherapy Research, 2022)
Introduction: The aim of this study was to present and discuss the knowledge gathered on various Achilles tendon injuries and to highlight the clinical implications for the evaluation and treatment of Achilles tendon injuries about the factors of Achilles tendon injuries. Study design: Systematic review. Materials and Method: A search of 5 databases including; Science Direct, Google scholar, PubMed, Ovid Medline, Scopus and Medline was performed using keywords related to Achilles tendon injury factors and a review of all usable manuscripts (the search was undertaken between 1980 to 2021). Result: One hundred and fifteen articles met the inclusion criteria. Among all the independent variables that were analyzed including age, obesity, athletes and normal people, professional or amateur sports, men and women, and Achilles tendon treatment methods were examined. Conclusion: Comparison of the prevalence of Achilles tendon injuries in athletes and non-athletes showed that the risk of Achilles tendon injuries were higher in 16-25 years old male than women, Also, the onset of injury in collision sports had the highest percentage.